BRAND EQUITY AND SERVICE QUALITY EFFECTS ON LOYALTY WITH AN INTERVENING VARIABLE OF CUSTOMER SATISFACTION - Rohani Rohani; Andi Hadidu; Sukardi Sukardi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study examines the effect of brand equity and service quality variables on customer loyalty with customer satisfaction as an intervening variable with a quantitative approach. The sampling technique used was purposive sampling, with 119 customers as respondents. The data analysis technique used is Partial Least Square (PLS) with the statistical method of Structural Equation Modeling (SEM). The results showed that there was a direct influence of brand equity and service quality variables on loyalty. Likewise, brand equity and service quality mediated by customer satisfaction have an effect on loyalty. This implies the importance of the role of brand equity, service quality, loyalty and customer satisfaction in supporting the existence and development of the GalaMart minimarket. Keywords: Brand Equity, Service Quality, Loyalty, Customer Satisfaction